URGENSI KEMAMPUAN KOMUNIKASI INTERPERSONAL YANG BAIK ANTARA STAKEHOLDER DAN PUSTAKAWAN DI PERPUSTAKAAN UMUM - Siti Bidayasari (Central Library of Universitas Sebelas Maret, 2018)
In the library communication activities are very important activities for librarians. Librarians are the spearhead in the service in the library. The research method used is the literature study model, for the data retrieval instrument the author uses a review or document review then the data obtained will be analyzed using a qualitative descriptive approach. The results showed interpersonal communication skills between stakeholders and librarians in the public library was important because with theestablishment of good and effective interpersonal communication, the relationship was developed, a sense of mutual need, and good cooperation was established, so that there was no more awkwardness, fear, laziness, and the gap between the head of the library and the librarian because the library head and librarian should be united and collaborate in developing the library even better